Dançar fechando: etnografia da Escola de Dança FUNCEB de Salvador - Ramos, Yasmine Ávila (Universidade Federal de São Carlos, 2019)
Bodies and dances are the key elements to understand this work: together, they create mouvements. These bodies move, learn, are modified, create; dances inform, expose, are updated. These two elements are together in a social space that disposes of particular dynamics that pass through it. But the bodies and the danses also create tonalities inside this space of learnership, FUNCEB’s dance school located in Pelourinho’s historical center. The movement in then to inform and be informed, to reproduce and to create, while also experimenting dance’s aspects that go beyond learning on class ou becoming a dancer professional. Dancers are continually being created, and they concatenate in theirs selves all these influences.
Closing Dance: ethnography of Salvador's FUNCEB Dance School
Keywords: Antropologia da dança; FUNCEB; Aprendizado; Corporalidade; Dançarino; Anthropology of dance; Learning; Corporality; Danser; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA URBANA